PSYCHOANALYSIS OF “DESDEMONA” CHARACTER ON OTHELO - Vera Kristiana (Fakultas Sastra UMN AL Washliyah, 2022)
This research is an analysis of one of the characters in the drama Othello, namely Desdemona. The analysis used is a psychological approach. Psychoanalysis was taken by the researcher because it was considered capable of explaining Desdemona's character in more detail. The purpose of this study is to find out how Desdemona's character in Othello is seen from a psychological point of view. This research method is descriptive qualitative and uses a literature study design. Data is taken from various sources; drama transcripts, articles, and others. Researchers use literature study because researchers indirectly analyze drama scripts, then use library research to obtain appropriate data as research information. The researcher chose Othello's drama as a data source, while the data for this study were all sentences and dialogues between characters in the drama script. The personality development of the character “Desdemona” shows that she is an independent woman who has the power to make some